Rescate de la comida ancestral del cantón Espejo, provincia del Carchi mediante la elaboración de una Guía Digital Gastronómica - Chalacán Cuaical, Erick David (2022)
The Espejo canton has an incomparable gastronomic resource for its variety of typical and ancestral dishes, in addition to having a variety of agricultural products that, due to their agro climatic floors, have a very characteristic quality and flavor. Since time immemorial, ancestral dishes have been an icon for the Espejo due to the use of characteristic utensils such as the chili grinding stone, wooden spoons and, above all, the famous potsherds and clay pots\; however, over the years and modernization, all these customs and traditions reflected in the ancestral gastronomy have been lost. That is why this research seeks to rescue those recipes, techniques, forms of preparation and ancestral dishes that are currently no longer very common to prepare, except for very few adults who continue to maintain this eating habit. For this, a documentary bibliographical research of local sources was carried out through which I compiled information on the history of local gastronomy, the most common ancestral dishes together with the preparation techniques and utensils. Qualitative information was obtained through interviews with the most influential people in the Espejo in order to obtain a local diagnosis on the situation regarding the loss of ancestral gastronomy\; With this information, a FODA analysis was designed to detect those problems, both internal and external to the Canton, in which the problem lies. Once the pertinent information was obtained, a digital gastronomic guide was designed using Adobe Illustrator Software, detailing the main ancestral dishes of the canton Espejo, their preparation method, ingredients and some illustrations.